Quaternary deposits and weathered bedrock material as a source of dangerous radon emissions in Estonia - Petersell, Valter; Jüriado, Krista; Raukas, Anto; Shtokalenko, Mihkel; Täht-Kok, Krista (Geologos, 2015)
The risk of dangerous radon emissions in Estonia is high, being among the highest in Europe. In almost 33 per cent of Estonian land area, the content of radon in soil-contained air exceeds the safe limit for unrestricted construction (50 kBq/m3). In such high radon-risk areas the concentration of radon in soil-contained air ranges from 50 to 400 kBq/m3, in a few cases reaching up to 2,100 kBq/m3 exceeding the permitted level for residential areas. The situation is particularly serious in the northernmost part of the country, where uranium-rich graptolite argillite (Dictyonema shale) and the Obolus phosphorite are close to ground surface and their particles are constituent parts of Quaternary deposits. Radon emissions from bedrock have been investigated in detail, but to date Quaternary strata as a source of radon emissions are poorly studied. According to our measurements the highest concentrations of radon are related to tills containing clasts and fines of graptolite argillite and phosphorite. Glacial deposits include also granitoidal material, containing U, Th and K, which have been transported by glaciers from the outcrop areas of crystalline basement rocks in Finland and the Gulf of Finland. Due to weathering, outwash and repeated redeposition other genetic types are poorer in radioactive elements and they are weaker sources of radon.